2006
DOI: 10.4319/lo.2006.51.3.1262
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic respiration and production in the meso- and bathypelagic realm of the eastern and western North Atlantic basin

Abstract: We measured prokaryotic production and respiration in the major water masses of the North Atlantic down to a depth of ,4,000 m by following the progression of the two branches of North Atlantic Deep Water (NADW) in the oceanic conveyor belt. Prokaryotic abundance decreased exponentially with depth from 3 to 0.4 3 10 5 cells mL 21 in the eastern basin and from 3.6 to 0.3 3 10 5 cells mL 21 in the western basin. Prokaryotic production measured via 3 H-leucine incorporation showed a similar pattern to that of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
186
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(208 citation statements)
references
References 56 publications
(72 reference statements)
17
186
5
Order By: Relevance
“…Recently, Aristegui et al (2009) reviewed deepwater prokaryotic abundance and activity and viral abundance and concluded that the variability in these parameters is as high in the deep ocean as in surface waters despite their decrease in average abundance by orders of magnitude over this depth range. In our study, heterotrophic prokaryotic activity decreased by three orders of magnitude from the epi-to the abyssopelagic layer and was generally similar to that reported for the deep waters of the southern region of the North Atlantic (Reinthaler et al, 2006). As mentioned above, heterotrophic prokaryotic activity was strongly related to viral abundance.…”
Section: Viral and Heterotrophic Prokaryotic Productionsupporting
confidence: 66%
See 1 more Smart Citation
“…Recently, Aristegui et al (2009) reviewed deepwater prokaryotic abundance and activity and viral abundance and concluded that the variability in these parameters is as high in the deep ocean as in surface waters despite their decrease in average abundance by orders of magnitude over this depth range. In our study, heterotrophic prokaryotic activity decreased by three orders of magnitude from the epi-to the abyssopelagic layer and was generally similar to that reported for the deep waters of the southern region of the North Atlantic (Reinthaler et al, 2006). As mentioned above, heterotrophic prokaryotic activity was strongly related to viral abundance.…”
Section: Viral and Heterotrophic Prokaryotic Productionsupporting
confidence: 66%
“…Viruses and prokaryotes in the deep (sub)tropical Atlantic D De Corte et al been reported previously (Allen and Bartlett, 2002;DeLong et al, 2006;Reinthaler et al, 2006). Lauro and Bartlett, 2008 showed that bathypelagic prokaryotes have generally a high copy number of rRNA operons per genome and a larger intergenic region.…”
Section: Discussionmentioning
confidence: 99%
“…Published estimates of POC flux attenuation with depth are, however, up to 2 orders of magnitude lower than corresponding estimates of heterotrophic metabolism [4][5][6][7] . This discrepancy indicates that either estimates of POC flux and/or community metabolism are unreliable, or that additional, unaccounted for, sources of organic carbon to the twilight zone exist 8 .…”
mentioning
confidence: 77%
“…For example, partitioning between the euphotic and aphotic regions has been amply documented for bacterioplankton processes (Carlson et al, 2004;Reinthaler et al, 2006) and for many major microbial plankton clades (Gordon and Giovannoni, 1996;Giovannoni et al, 1996;Wright et al, 1997;DeLong et al, 2006). Evolutionary adaptive radiation into ecotypes that are specialized to specific depth horizons has also been previously described as niche partitioning for SAR11 and Prochlorococcus (Field et al, 1997;Moore et al, 1998).…”
Section: Discussionmentioning
confidence: 99%